Incubators and technical valleys in gifted education in Saudi universities: Feasibility of employment and perceptions of digital support - Saleh, Shoeb; Al-Qahtani, Mohammed (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the extent to which gifted students at Saudi universities benefit from incubators and technology valleys, using a descriptive-analytical approach to define the conceptual framework and analyze indicators of their utilization in gifted education. The analysis focuses on three key dimensions: the availability of information and logistical services connecting students with these facilities, the quality of support provided, and the provision of diverse assistance services, including technical, financial, administrative, advisory, and marketing support. Statistical analysis of faculty responses reveals a moderate level of utilization. The research recommends establishing clear performance measurement criteria and improving communication mechanisms between students and these entities. Additionally, it proposes a digital and network-based support framework to enhance students' capabilities and create an integrated learning environment.